2021
DOI: 10.1016/j.jbc.2021.100883
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor receptor beta activates Abl2 via direct binding and phosphorylation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We speculate that this is due to the synthetic surface-HA receptor, which was generated using a truncated PDGFRb transmembrane domain. In contrast to HEK293 cells 38 , PDGFRb is not endogenously expressed in Jurkat cells, which may interfere with the internalization and turnover rate of this receptor on Jurkat cells. As DIRECTED relies on receptors that can efficiently be endocytosed, this could result in inefficient internalization.…”
Section: Resultsmentioning
confidence: 96%
“…We speculate that this is due to the synthetic surface-HA receptor, which was generated using a truncated PDGFRb transmembrane domain. In contrast to HEK293 cells 38 , PDGFRb is not endogenously expressed in Jurkat cells, which may interfere with the internalization and turnover rate of this receptor on Jurkat cells. As DIRECTED relies on receptors that can efficiently be endocytosed, this could result in inefficient internalization.…”
Section: Resultsmentioning
confidence: 96%
“…The list of empirically determined ABL2 activators is relatively short, including Src, EGFR, PDGFRβ, AXL, ERBB2, ERBB3, ERBB4, FLT3, and c-Met. 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 Of these, PDGFRβ has been shown to be activated in liver fibrosis as well as other liver pathologies and has recently been demonstrated to engage in bidirectional signaling with ABL2. 13 , 87 , 88 Our lab has preliminary data indicating alcohol promotes both PDGFRβ as well as its ligand PDGFβ, both of which are significantly suppressed by ABL2 knockdown ( Figure 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we found that the Abl2 C-terminal half is significantly disordered and has two distinct sites for tubulin binding ( Figure 2 ). Phase separation appears to be a common feature of diverse MT regulators including TPX2 18,76 , tau 59,60,77 , and CLIP-170 78 , with diverse activities including MT nucleation, protection of MT severing, and condensing tubulin dimers for MT growth. We showed that new MTs nucleated from Abl2-eGFP:tubulin co-condensates.…”
Section: Discussionmentioning
confidence: 99%
“…In its kinase-inactive conformation, the Abl2 N-terminal half adopts a locked conformation in which its N-terminal Src homology (SH) 3, SH2, and kinase domains engage in the intramolecular interactions that inhibit kinase activity [79][80][81][82] . Signaling through integrin and growth factor receptors is believed to relieve this inhibition and trigger extensive phosphorylation of downstream effectors 78,[83][84][85] . It is unclear how phase separation would impact the ability of Abl2 to interact with upstream activating receptors or its substrates.…”
Section: Does Phase Separation Impact Abl2 Kinase Signaling?mentioning
confidence: 99%